Peer Social Support, Personality Type, and Smoking Tendency in SMK(T) Students in Sidoarjo District - Lely Ika Mariyati; Nur Habibah (Universitas Muhammadiyah Sidoarjo, 2015)
Smoking is a one of a juvenile delinquency. However, if it is not handled properly, it will have an impact on adolescent tendency to a higher juvenile. The aim of this study was to determine the relationship between peer social support and personality type with a trend of smoking on SMK Students in Sidoarjo. The hypothesis was that there is a positive relationship between social support of SMK Students (T) with a trend to smoke, there is a positive correlation between the personality type of vocational students (T) with a trend to smoke, and there is a positive relationship between social support and personality type with a trend to smoke. This research used three variables: two independent variables X1: peer social support, X2: personality type; and the dependent variable Y: the trends in smoking of SMK Students in Sidoarjo. The research data analysis used multiple correlation technique using SPSS 16.0 for Windows. The results obtained with the correlation coefficient ρ-0.073 (0.146)> 0.05, meaning that peer social support variables relationship with smoking trends were not significant; the correlation coefficient r with ρ 0.006 (0.904)> 0.05, meaning that the personality type variable relationship with smoking trends were not significant. These results showed that the hypothesis of the reseach were not proven.